Investigating student difficulties on integral calculus based on critical thinking aspects - Farida Nursyahidah; Irkham Ulil Albab (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2017)
Students of Mathematics education often struggle with integration problem, but yet the root of the problem related to critical thinking is rarely investigated. This article reports research where the first-year students of Mathematics Education of PGRI University Semarang were given an integral problem, then individually they were interviewed related to the answer they have made. The findings of students' difficulties in working on integration problem were confirmed through several questions in the interview which aimed to uncover their critical thinking process related to concepts, procedures, and problem solving. This study shows that student difficulties in Integration by disc method such as failure in identifying radius of a rotary object, specify partition, and integration bounds are closely related to their failure to think critically related to concept, skills, and problem solving aspects of critical thinking.